The science book of energy - Ardley, Neil. (San Diego : Harcourt Brace Jovanovich, 1992)
Gives instructions for a variety of simple experiments that explore and explain different forms of energy.
"Gulliver books.".
Book Links (A.L.A.).
5.5.
5.5
3-6
Keywords: Force and energy -- Experiments -- Juvenile literature; Experiments; Force and energy -- Experiments; Force and energy -- Experiments; Science -- Experiments